Diversity in the soil virosphere: to infinity and beyond?. Issue 11 (November 2022) - Roux, Simon; Emerson, Joanne B.
Abstract : Viruses are key members of Earth's microbiomes, shaping microbial community composition and metabolism. Here, we describe recent advances in 'soil viromics', that is, virus-focused metagenome and metatranscriptome analyses that offer unprecedented windows into the soil virosphere. Given the emerging picture of high soil viral activity, diversity, and dynamics over short spatiotemporal scales, we then outline key eco-evolutionary processes that we hypothesize are the major diversity drivers for soil viruses. We argue that a community effort is needed to establish a 'global soil virosphere atlas' that can be used to address the roles of viruses in soil microbiomes and terrestrial biogeochemical cycles across spatiotemporal scales. Highlights: Targeted soil viral metagenomes (viromes) enable in-depth exploration of encapsidated genetic material in soil. Extra-large-scale combined assemblies can reveal rare viruses otherwise missed from total metagenomes. RNA-based metatranscriptomes and viromes provide insights into substantial RNA virus diversity in soil. Viromics combined with laboratory approaches for evaluating viral activity and virus–host interactions, including controlled incubations, cultivation, single-cell approaches, and microscopy, will form the framework for addressing long-standing soil viral ecology questions. We posit that soils represent the 'perfect storm' of diversity drivers, including spatiotemporal dynamics, physicochemical heterogeneity, and occasional immigrations, resulting in highly diverse and dynamic viral communities.